A Sketch on the Balkans as a “Centre of Peripheries” - Raymond Detrez (Zeszyty Cyrylo-Metodiańskie)
Throughout its history, the Balkan Peninsula has been encompassed within various expansive cultural and historical spheres, as well as state-like political formations. The most prominent among these include the ancient world, the Roman Empire, the Byzantine commonwealth, the Ottoman Empire, modern Europe, the Soviet bloc, and the European Union. Additionally, the region has experienced influences from less dominant spheres such as the Eurasian steppe, the Arab world, and the maritime empires of the Italian city-states and Dubrovnik. Within these broader frameworks, the Balkans have frequently occupied a peripheral position, characterized by frequent interactions with neighbouring cultural zones and limited control from the normative centre. These interactions, coupled with the region’s unique relationship to cultural and political centers, have contributed to the formation of distinct cultural hybrids. This paper explores several examples that substantiate the thesis of the Balkan Peninsula as a site of cultural hybridity. Original title in Bulgarian: Хибридните Балкани като ‘център на периферии’ – една скица.